IMPLEMENTASI MANAJEMEN MUTU DALAM MENGEMBANGKAN BUDAYA RELIGIUS DI MTS MADRASATUL QUR’AN JOMBANG - Nisa', Khoirun; Masrudin, Imam Ma'ruf (Universitas KH. A. Wahab Hasbullah, 2021)
The quality of education will be achieved, if it is supported by all components of education which are held with all considerations. Some of these components are inputs, processes, and outputs, and need full support from parties who have important roles in educational institutions. However, one thing that is the focus here is that the quality of education has so far been assessed by learning achievement, outputs received at superior universities, and so on, moreover, it is added with indicators of religious points which are internalized in students. Since religious values ​​are internalized in students, even though students who have sky-high achievements will eventually become the new Gaius Tambunan. Departing from this, it is therefore very urgent for educational institutions, especially educational institutions to internalize religious values ​​into independent learners by using inuring through religious culture.